Les amours imaginaires [videorecording (DVD)] - Dolan, Xavier; Dolan, Xavier; Dolan, Xavier; Dolan, Xavier; Dolan, Xavier; Chokri, Monia; Schneider, Niels (distributed by MPI Media Group ; Sundance Selects : IFC Films, 2011)
"It's hipster sexual politics filtered through the French New Wave[.] .... When Francis and his best friend Marie both fall for the same guy, all bets are off as they attempt to out-maneuver one another to win his affection. Or at least figure out what his sexual preferences are and who's got a shot."--Container.